The Two-Tier Fecal Occult Blood Test: Cost-Effective Screening - Andrew J Rae; Iain GM Cleator (Canadian Journal of Gastroenterology)
The two-tier test represents a strategy combining HO Sensa and Hemeselect fecal occult blood tests (FOBTs) with the aim of greater specificity and consequent economic advantages. If patients register a positive result on any HO Sensa guaiac test, they are once again tested by a hemoglobin-specific Hemeselect test. This concept was applied to a multicentre study involving persons 40 years or older. One component of the study enrolled 573 high risk patients while the second arm recruited an additional 1301 patients (52% asymptomatic/48% symptomatic) stratified according to personal history and symptoms. The two-tier test produced fewer false positives than traditional tests in both groups evaluated in the study. In the high risk group, specificity (88.7% for two-tier versus 80.6% for Hemoccult and 69.5% for HO Sensa) was higher and false positive rates were lower (11.3% for two-tier versus 19.5% for Hemoccultand 30.5% for HO Sensa) for the two-tier test versus Hemoccult and HO Sensa FOBTs (95% CI for all colorectal cancers [CRCs] and polyps greater than 1 cm, α=0.05 ). No significant differences in sensitivity were observed between tests in the same group. Also, in the high risk group, benefits of the two-tier test outweighed the costs. Due to the small number of cancers and polyps in the second arm of the study, presentation of data is meant to be descriptive and representative of trends in a ‘normal’ population. Nevertheless, specificity of the two-tier test was higher (96.8% for two-tier versus 87.2% for Hemoccult and 69.5% for HO Sensa) and false positive rate lower (3.2% for two-tier versus 12.8% for Hemoccult and 22.3% for HO Sensa) than either the Hemoccult or HO Sensa FOBT (95% CI for all CRCs and polyps greater than 1 cm). This initial study, focusing on the cost-benefit relationship of increased specificity, represents a new way of economically evaluating existing FOBTs.